Operating room time savings in Germany- and UK-based hospitals with 3D- VS. 2D-imaging technology in laparoscopic surgery: Meta analysis and budget impact model – Health economic evaluation. (June 2022) - Wahba, R.; Urbanski, A.; Datta, R.R.; Kleinert, R.; Bruno, L.; Zervakis, A.; Thomas, M.N.
Abstract: Aims: Opportunity cost (OC) analysis is key when evaluating surgical techniques. Operating room (OR) time is one potential source of OC in laparoscopic surgery. This study quantifies differences in OR time between 3D- and 2D-imaging technology in laparoscopic surgery, translates these into OC and models the economic impact in real-world hospitals. Methods: First a systematically performed literature review and meta-analysis were conducted. Then, methods to translate OR time savings into OC were theorised and a budget impact model was created. After that, the potential time savings of real-world hospital case mixes were extrapolated. Finally, the opportunity costs of not using 3D-imaging in laparoscopic surgery were evaluated. Results: Average OR time saving per laparoscopic procedure was −19.4 min (−24.3; −14.5) (−14%) in favour of 3D. The Budget Impact Model demonstrated an economic impact of using 3D-laparoscopy instead of 2D laparoscopy, ranging from £183, 045-£866, 316 in the British and 73, 049€-437, 829€ in German hospitals, modelling a mixture of cost savings and performing additional procedures (earning additional revenue). Conclusion: The OC analysis revealed significant economic benefits of introducing 3D-imaging technology in laparoscopic surgery, on the basis that average procedure time is reduced. Utilising the saved OR time to perform additional procedures was the biggest driver of OC. Hospital case mix and procedure volume indicated the magnitude of the OC.